(untitled) (International Journal of Engineering and Computer Science, 2017)
In case of sharing the group of documents in cloud storage the document owners uses the encrypted key for secured sharing. For a single owner, the document contains one trapdoor key then the user can download it using the key, but for multiple owners this concept does not works. To overcome this practical problem this paper proposes a solution for KASE in case of federated clouds. This is a practice of interconnecting the cloud computing environment of two or more service providers for the purpose of load balancing traffic.